IMPROVING STUDENTS’ DIRECT AND INDIRECT SPEECH MASTERY IN NEWS ITEM TEXT THROUGH USING INPUT ENHANCEMENT TECHNIQUE - Muhammad Mujtaba Mitra Zuana (Jurnal Pendidikan, 2021)
The goal of this research is to find out whether input enhancement technique is effective in improving students’ direct and indirect speech mastery in news item text. This research is quantitative experimental research with pretest and posttest control group design. The data of this research is the students’ direct and indirect speech mastery in new item text. The data collection technique is by administering tests, using pretest-posttest design. The data analysis technique uses t-test formula. The result indicates that there was no difference between control and experimental group in initial abiity before the input-enchancemen-technique was treated. Whereas by using input enhancement technique there was significant difference between students taught direct and indirect speech mastery using input enhancement technique and those taught direct and indirect speech mastery in news item text without using input enhancement technique. Thus, it could be concluded that the use of input enhancement technique was effective in improving students’ direct and indirect speech mastery in news item text. Penelitian ini dilakukan untuk mengetahui apakah penggunaan teknik peningkatan input efektif dapat meningkatkan penguasaan tuturan siswa secara langsung dan tidak langsung pada teks item berita. Penelitian ini merupakan penelitian eksperimental kuantitatif dengan desain control group pretest and posttest. Data dalam penelitian ini adalah penguasaan tuturan langsung dan tidak langsung siswa pada teks item berita. Teknik pengumpulan data dengan pemberian tes, pretest dan posttest. Teknik analisis data menggunakan rumus uji-t. Hasil penelitian menunjukkan bahwa tidak ada perbedaan antara kelompok kontrol dan kelompok eksperimen dalam hal kemampuan awal sebelum dilakukan perlakuan teknik input-enhancemen. Sedangkan dengan menggunakan teknik peningkatan input terdapat perbedaan yang signifikan antara hasil belajar siswa dalam hal penguasaan tuturan langsung dan tidak langsung menggunakan teknik peningkatan input dengan hasil belajar siswa dalam hal penguasaan tuturan langsung dan tidak langsung dalam teks item berita tanpa menggunakan teknik peningkatan input. Dengan demikian, dapat disimpulkan bahwa penggunaan teknik peningkatan input efektif dalam meningkatkan penguasaan tuturan siswa secara langsung dan tidak langsung pada teks item berita.